Confirmatory Factor Analysis (CFA) To Measure Competitive Advantage in Tourism Village From Supply Tourism Perspectives - Ayu Esteka Sari; Gampo Haryono; Reni Yuliviona (Cita konsultindo, 2024)
The competitiveness of the tourism sector is the capacity of tourism businesses to attract foreign and domestic visitors visiting a particular tourist destination. Increasing competitiveness can be achieved by utilizing existing resources, improving management capabilities so that they have competitiveness. The purpose of this study is to analyze Competitive Advantage in Tourism Village From Supply Tourism Perspectives using Confirmatory Factor Analysis (CFA) analysis. The population in this study is visitors from tourist attractions in the tourist village of Apar, with the number of samples is 100 respondents. Analysis of the Confirmatory factor analysis (CFA) method was performed using AMOS 25. The result of the construct reliability (CR) value of the latent variable natural resources and environment with the result is 0.7296. The result of the construct reliability (CR) value of the latent built environment variable with the result is 0.7018. The result of the construct reliability (CR) value of the latent variable Operating Sectors with the result is 0.81006 and the result of the construct reliability (CR) value of the latent variable of hospitality and cultural resources produces a value of 0.9558.